Antifibrotic effect and long‐term outcome of SGLT2 inhibitors in patients with NAFLD complicated by diabetes mellitus. Issue 11 (30th August 2022) - Arai, Taeang; Atsukawa, Masanori; Tsubota, Akihito; Mikami, Shigeru; Haruki, Uojima; Yoshikata, Keiichiro; Ono, Hiroki; Kawano, Tadamichi; Yoshida, Yuji; Tanabe, Tomohide; Okubo, Tomomi; Hayama, Korenobu; et al.
Abstract: The aim of this retrospective multicenter study was to clarify the antifibrotic effect and long‐term outcome of sodium glucose cotransporter 2 inhibitors (SGLT2‐Is) in patients with nonalcoholic fatty liver disease (NAFLD) complicated by type 2 diabetes mellitus (T2DM). Of the 1262 consecutive patients with T2DM who recently received SGLT2‐Is, 202 patients with NAFLD had been receiving SGLT2‐Is for more than 48 weeks and were subjected to this analysis. Furthermore, 109 patients who had been on SGLT2‐I therapy for more than 3 years at the time of analysis were assessed for the long‐term effects of SGLT2‐Is. Significant decreases in body weight, liver transaminases, plasma glucose, hemoglobin A1c, and Fibrosis‐4 (FIB‐4) index were found at week 48. Overall, the median value of FIB‐4 index decreased from 1.42 at baseline to 1.25 at week 48 ( p < 0.001). In the low‐risk group (FIB‐4 index < 1.3), there was no significant change in the FIB‐4 index. In the intermediate‐risk (≥1.3 and <2.67) and high‐risk (≥2.67) groups, the median levels significantly decreased from 1.77 and 3.33 at baseline to 1.58 and 2.75 at week 48, respectively ( p < 0.001 for both). Improvements in body weight, glucose control, liver transaminases, and FIB‐4 index were found at 3 years of SGLT2‐I treatment. In the intermediate‐risk and high‐risk groups (≥1.3 FIB‐4 index), the FIB‐4 index maintained a significant reduction from baseline throughout the 3 years of treatment. Conclusion: This study showed that SGLT2‐Is offered a favorable effect on improvement in FIB‐4 index as a surrogate marker of liver fibrosis in patient with NAFLD complicated by T2DM, especially those with intermediate and high risks of advanced fibrosis, and this antifibrotic effect is sustained for the long term. Abstract : SGLT2‐Is treatment is useful for improving liver fibrosis in patients with NAFLD complicated by T2DM, especially those with intermediate and high risks of advanced fibrosis, and this anti‐fibrotic effect is sustained for long term.image